APPLICATION OF BOILED BEAN WATER IN REDUCING BLOOD SUGAR LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Syarkawi Syarkawi (Universitas Bina Bangsa Getsempena, 2024)
Type II diabetes is metabolic disorder stemming from endocrine marked with a glycemic imbalance. Decoction of soursop leaves is an intervention in lowering blood sugar levels in patients with type 2 diabetes mellitus. To prevent such complications, it could be overcome with one of the non - pharmacological therapies used in bean stew. The study was intended to illustrate the application of beans' boiled water in reducing blood sugar in diabetes patients with type 2. Respondents in this study were 2 diabetes mellitus patients with the criteria of diabetes mellitus patients who were willing to be respondents and were cooperative, composmentist awareness, famale aged 40-45 years, who experienced increased blood sugar (>200 mg/dL). Research has found that bean stew therapy is effective in reducing blood sugar in diabetes patients. On the subject I was given a blood-sugar therapy 382 milligrams is moderate after administering blood-sugar therapy to 300 milligrams. And the subject will be obtained before treatment with blood sugar levels of 260 mg/ dl, while administered with blood-sugar therapy to 207 mg/ dl. It is hoped that these bean stew water can be one of the non-pharmacological therapies used in reducing blood sugar in type 2 diabetes patients.